2005
DOI: 10.1007/s00792-005-0456-1
|View full text |Cite
|
Sign up to set email alerts
|

Community phylogenetic analysis of moderately thermophilic cyanobacterial mats from China, the Philippines and Thailand

Abstract: Most community molecular studies of thermophilic cyanobacterial mats to date have focused on Synechococcus occurring at temperatures of approximately 50-65 degrees C. These reveal that molecular diversity exceeds that indicated by morphology, and that phylogeographic lineages exist. The moderately thermophilic and generally filamentous cyanobacterial mat communities occurring at lower temperatures have not previously been investigated at the community molecular level. Here we report community diversity in mats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Cyanobacteria are the most commonly reported microbial group constituting these mats and they are considered the major primary producers in these habitats (Castenholtz 1973). Synechococcus-like representatives are the Cyanobacteria usually found at the highest temperatures (up to 74°C; Hongmei et al 2005;Ward and Castenholz 2000). Other bacteria share these environments with the Cyanobacteria and have important roles within these microbial communities (Moyer et al 1995;Ward et al 1990;Weller et al 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Cyanobacteria are the most commonly reported microbial group constituting these mats and they are considered the major primary producers in these habitats (Castenholtz 1973). Synechococcus-like representatives are the Cyanobacteria usually found at the highest temperatures (up to 74°C; Hongmei et al 2005;Ward and Castenholz 2000). Other bacteria share these environments with the Cyanobacteria and have important roles within these microbial communities (Moyer et al 1995;Ward et al 1990;Weller et al 1992).…”
Section: Introductionmentioning
confidence: 97%
“…1 Microorganisms can live in environment along with human and in extreme conditions such hot springs, miles deep in the ocean, inside rocks and in extreme cold temperature. 2 Although the number of microorganisms varies in different places, it has been indicated that mass of carbon from these microorganisms could be trillions of tons. [3][4][5] Correspondence to: Kohinur Begum E-mail: prof.kohinur@asaub.edu.bd/kohinur025@yahoo.com Dhaka Univ.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, great sequence variability of the 16S rRNA gene has been found among Calothrix strains from the Baltic Sea (Sihvonen et al, 2007), suggesting that they belong to at least five different genera. Hongmei et al (2005) showed that a single morphotype of Calothrix in thermophilic cyanobacterial mats comprised five different 16S rRNA genotypes. The tree topology obtained from phylogenetic analysis of cyanobacterial 16S rRNA gene sequences in our study was in agreement with that of Sihvonen et al (2007) and supported the idea that members of the genus Calothrix are polyphyletic and should be divided into several different genera.…”
Section: Molecular Fingerprinting Analysis -Tggementioning
confidence: 99%